Hukuman Mati Perspektif Al-Qur’an dan Hak Asasi Manusia: Analisis Komparatif - Ahmad, Amiril; Arief, Syaiful (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Death Penalty in the Perspective of the Quran and Human Rights: A Comparative AnalysisThe law of qishash has drawn considerable attention from Human Rights activists due to the perception that the death penalty is incompatible with modern life, seen as highly inhumane and cruel. Conversely, qishash, as a divine law, is deemed obligatory, with non-compliance resulting in individuals being labeled as disbelievers, oppressors, and transgressors. This study explores how the Quran and Human Rights perceive the death penalty and investigates points of convergence and divergence between them. Using a qualitative, descriptive analysis approach, the research draws information from diverse sources, including documents, journals, scholarly works, and relevant books. Findings reveal disparities between anthropocentric and theocentric perspectives in interpreting the death penalty. From a Human Rights standpoint, the death penalty serves as a means to ensure societal safety and the right to life, aligning with Human Rights' core values emphasizing the sanctity of life. Moreover, the Quran, a significant Abrahamic religious text, promotes the preservation of life, with its ordinances understood as beneficial to humanity, as Allah is considered humanity's ultimate purpose. In essence, despite debates over the death penalty's application, both Human Rights and the Quran, with its divine legal standing, share a common goal of safeguarding and guaranteeing human life. Consequently, they fundamentally converge on this matter.